Pengaruh Tingkat Perputaran Kas dan Kecukupan Modal Terhadap Profitabilitas Pada Lembaga Perkreditan Desa di Kecamatan Tegallalang - Wiadnyani, Ni Made; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This study aimed to examine the effect of capital adequacy and cash turnover on profitability. This study used causal quantitative research. The population in this study was the Lembaga Perkreditan Desa (LPD) in the Tegallalang district, within the total number of 45 LPD. The sample size of this study was 39 LPD, and the sampling technique being used was purposive sampling, so the type of useable data was quantitative data, secondary data sources, and data aggregation. Multiple linear regression was the analysis technique in this data. The results showed that (1) cash turnover affected profitability. (2) Capital adequacy affected profitability. (3) The level of cash turnover and capital adequacy affected profitability simultaneously. The higher the cash turnover, the more the cash re-entry through sales could be used to fund the company's operational activities. Therefore, the financial condition of LPD would be maintained, and the profitability also would be increased. This showed that the higher the capital adequacy, the more LPD will be able to take the existing risks and be able to avoid the company from existing losses.